Odpowiedzi

Najlepsza Odpowiedź!
2010-02-04T16:09:44+01:00
A) 5a+10b-15c = 5(a + 2b - 3c)
b)12x+5xy+8x² = x(12 + 5x + 8x)
c)5a²+15a+20a³ = 5a(a + 3 + 4a²)
d)8a³-4a²-8a+4 = 4(2a³ - a² - 2a + 1)
e)-3k-6k³-18klm = -3k(k + 2k² + 6lm)
f)-0,25x-0,75y-1,5 = -0,25(x + 3y + 6)
g)5a+0,7a²+10abc = a(5 + 0,7 + 10bc)
h)10x⁴+50x²-100x³ = 10x²(x² + 5 - 10x)
1 5 1
2010-02-04T16:14:00+01:00
A) 5(a+2b-3c)
b) x(12+5y+8x)
c)5a(a+3+4a²)
d) 4(2a³-a²-2a+1)
e)-3k(1+2k²+6lm)
f) -0,25(x+3y+6)
g) a (5+0,7a+10bc)
h)10x²(x²+5-10x)
1 5 1
2010-02-04T17:07:09+01:00
A) 5a+10b-15c
5(1a+2b-3c)
b)12x+5xy+8x²
1/2x(6+2,5y+4x)
c)5a²+15a+20a³
5a(1a+3a+5a²)
d)8a³-4a²-8a+4
4(2a³-a²-2a+1)
e)-3k-6k³-18klm
-3k(1+2k²+6lm)
f)-0,25x-0,75y-1,5
-0,25(x+3y+6)
g)5a+0,7a²+10abc
a (5+0,7a+10bc)

h)10x[do czwartej potęgi]+50x²-100x³
10x²(x²+5-10x)